OPTIMASI KONDISI UNTUK RENDEMEN HASIL EKSTRAKSI KULIT MANGGIS (Garcinia mangostana L.) Optimization of Conditions for Yield Extraction of Mangosteen Pericarp (Garcinia mangostana L.) - Endang Zainal Hasan, Akhmad; Nashrianto, Husain; Novia Juhaeni, Rani (FITOFARMAKA | Jurnal Ilmiah Farmasi, 2012)
The aim of this study is to determine the levels of yield extract of mangosteen pericarp extracted using Response Surface Methodology (RSM) Central Composite Design (CCD) with various concentrations of ethanol (in the range of 45 to 96 %) and duration of microwave heating (in the range 5.8 to 34.1 o C) or Microwave Assisted Extraction (MAE). The yield extract was calculated as percentage to the weight of origin. The results showed that optimum extraction conditions for yield extract were at ethanol concentration of 70% and heating time of 31.5 minutes which resulted in yield extract of 19.45%. More over, under these conditions resulted yield of 19.83%. The yield extract equation of mangosteen pericarp is Y = -73,7883 + 0,5293 X heating time and X 2 1 + 2,4230 X 2 is ethanol concentration in water as solvent. – 0,0084X12 – 0,00173 X2 2 , where X1 is  heating time and X2 is ethanol concentration in water as solvent. Key words : Optimization, Mangosteen, RSM CCD, MAE, yield